Penggunaan model numbered heads together (NHT) untuk meningkatkan sikap sosial kerjasama pada peserta didik kelas II sekolah dasar - Priagung, Kiky (Universitas Sebelas Maret, 2020)
This research aims to improve social cooperation through application of the Numbered Heads Together model. This study is Classroom Action Research with three cycles. The research subject were students 2th grade of Pajang IV state primary school Surakarta in the 2019/2020 academic year, with a total 17 students. This study uses data collection technique in the form of interview, observation, questionnaire, peer to peer assesment, and documentation with data analysis of content validity and triangulation. Analysis of the data used is the Miles-Huberman interactive analysis model. Classical completeness results the first cycle reaches 47%, classical completeness of the second cycle reaches 65%, and the third cycle produces a percentage 82%. Based on the results of the study, can be concluded that social cooperation on 2th students Pajang IV state primary school Surakarta in the 2019/2020 academic year can be improved through the numbered heads together model. The result of this study have contributed to the world of education as one alternative to solving the affective realm, especially social attitudes of cooperation.